I saw it in in the news today: a content analysis of drowning in Western Australian news media over two summers - Leavy, Justine; Crawford, G.; Della Bona, M.; Nimmo, L.; Jancey, J. (BMJ PUBLISHING GROUP, 2018)
Fatal drowning events are often reported in news media. In Australia news articles are a key source of health information. Media exposure has been shown to influence people’s health behaviours and helps to set the public agenda. This study examines coverage of fatal drowning events in newspapers, in Western Australia (WA). WA coronial data were collected for age, gender, location and description of fatal event for two time periods: 1 December to 31 March 2015 and 2016 (southern hemisphere summer). A three-step approach was utilised to capture corresponding news articles: (1) Media Alert monitoring reports; (2) Google News; and (3) Factiva. A coding protocol extracted: newspaper name, print/digital, page news angle, and population group, responsibility for the drowning event and drowning prevention, event outcome and prevention strategies. A final sample comprised 50articles (60% print and 40% digital). Articles matched 17 individual fatal drowning events, almost half (n=23) related to one toddler drowning incident. Stories rarely appeared on page 1 (n=2), but were in the first 2–10 pages 20/50 (66.6%). Celebrating ‘lives lost’ with testimonials was a common news angle (22%). There were 18 mentions of potential drowning prevention strategies, swimming between the flags was most frequently nominated (n=4). Drowning experts were cited 12 times in 18 news articles. This study found drowning events were considered newsworthy by WA news outlets, however focussed on the personal characteristics of the deceased and did not use the opportunity to put drowning prevention at the top of the public agenda. The paucity of page one stories suggests drowning is not high on the news agenda. Drowning prevention experts were only consulted or quoted sporadically. We must take the opportunity to better engage news media outlets to increase the dissemination of drowning prevention messages.